Recovery, medication and shared responsibility in mental health care. (December 2013) - Stratford, Anthony; Brophy, Lisa; Beaton, Tracy; Castle, David
Objective: The recovery paradigm is significantly influencing contemporary mental health services. This paper explores using a recovery orientation when introducing, prescribing, administering and monitoring medication as part of treatment in psychiatry. Conclusions: Recovery is not 'anti' medication; however, a recovery-oriented position does require the adoption of an enabling and empowering approach to the use of medication. The cornerstone of this is shared decision-making that respects the person's own lived experience and choice as well as the practitioner's professional expertise. This paper suggests that by taking this path, relationships between psychiatrists, other clinicians and consumers will be enhanced.